The Role of the ASICC-SLICES Model in Promoting Science Literacy and Collaboration Skills: A Pathway to Educational Sustainable Development - Haka, Nukhbatul Bidayati; Leoninda, Alfiyani; Solviana, Meita Dwi; Masya, Hardiyansyah; Hidayah, Nur (Universitas Islam Negeri Ar-Raniry, 2025)
The lack of science literacy and collaboration skills can hinder high school students in facing global challenges and supporting environmental sustainability actions. Therefore, developing science literacy and collaboration skills is crucial, particularly in biology education. The ASICC-SLICES model (Adapting, Searching, Interpreting, Creating, and Communicating based on Science Literacy Circles) enhances students' science literacy and collaboration skills. This quasi-experimental study, using a pretest-posttest control group design, aims to evaluate the effect of the ASICC-SLICES model on improving students' science literacy and collaboration skills and its contribution to Educational Sustainable Development. The study population consisted of tenth-grade students from a public high school in Lampung, with a sample of 70 students obtained using the Cluster Random Sampling technique. The research instruments included a science literacy test, questionnaires, observation sheets for collaboration skills, and documentation. Data were analyzed using MANOVA with an α of 0.05. The results showed that the implementation of the ASICC-SLICES model significantly improved students' science literacy and collaboration skills, with n-gain scores for the experimental and control groups (sig) 0.000<0.05 (α). These findings indicate that the ASICC-SLICES model contributes positively to students' awareness and actions in supporting environmental sustainability